2015
DOI: 10.14814/phy2.12644
|View full text |Cite
|
Sign up to set email alerts
|

Routine daily physical activity and glucose variations are strongly coupled in adults with T1DM

Abstract: Type 1 Diabetes (T1DM) is characterized by altered glucose homeostasis resulting in wide glucose variations throughout a 24‐h period. The relationship between routine daily physical activity and glucose variations has not been systematically investigated in adults with T1DM. The objectives of this study were to characterize and quantify the relationship between routine daily activity and glucose variations in a small group of adults with T1DM. Adults with T1DM treated with an insulin pump were recruited for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The fluctuations in the glucose level and OSA features after sleep onset can be decomposed into different frequency components, and the time-varying coherence between the two signals can be calculated at each underlying frequency. Previous studies showed dynamic coupling between CGM data and physical activity 15 or electroencephalogram (EEG) power 16 during sleep in patients with type 1 diabetes mellitus using wavelet coherence analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The fluctuations in the glucose level and OSA features after sleep onset can be decomposed into different frequency components, and the time-varying coherence between the two signals can be calculated at each underlying frequency. Previous studies showed dynamic coupling between CGM data and physical activity 15 or electroencephalogram (EEG) power 16 during sleep in patients with type 1 diabetes mellitus using wavelet coherence analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first study to use a tool that can be used to classify exercise as anaerobic, anaerobic or mixed. This may help a number of groups who are currently working on AP development for exercise (25,26,27).…”
Section: Commentmentioning
confidence: 99%
“…In people with type 1 diabetes, slow-pace walking after a meal improves postprandial glucose excursions when observed in controlled study environment (Manohar et al, 2012). Routine daily PAs of everyday life seem to be coupled with glucose variations in type 1 diabetes (Farabi et al, 2015). Recent study has successfully provided quantitative information on correlation between mild PA and short-term glucose dynamics in type 1 diabetes (Zecchin et al, 2013), that could be used in future models to improve glucose management with combination of advanced sensor technologies (Ding and Schumacher, 2016).…”
Section: Introductionmentioning
confidence: 99%